Enhanced thermal and mechanical properties of optimized SiCf/SiC composites with in-situ CNTs on PyC interface. Issue 11 (1st August 2020) - Li, Zhexin; Li, Xiaoqiang; Zhang, Boxin; Zhou, Xianguo; Liu, Chuanxin; Jiang, Yu; Zhen, Cheng; Zheng, Ce; Zhang, Litong; Cheng, Laifei
Abstract: In this work, carbon nanotubes (CNTs) were introduced on the pyrolytic carbon ( PyC ) interface via chemical vapor deposition (CVD) in order to improve the thermal conductivity and mechanical properties of SiC f / SiC composites. The results showed that three major parameters of CVD (a.k.a the deposition temperature, volume fraction of C 2 H 4 and deposition duration) strongly affected the nature of CNTs, as well as the thermal conductivity and mechanical properties of SiC f / SiC composites. The optimal parameters of CVD were found to be 800 °C, 15 vol% C 2 H 4 and 10-30 min. The thermal conductivity and mechanical properties of SiC f / SiC composites were enhanced by the addition of CNTs. However, the excessive deposition of CNTs provoked the formation of pores in the matrix, resulting in the reduction of the thermal conductivity and mechanical properties. The deposition of 5.8 vol % CNTs (corresponding to 20 min CVD deposition) was found to be the best condition to improve the thermal conductivity and mechanical properties of SiC f / SiC .